Green Human Resources Management and employees' green behavioral intention: the role of individual green values and corporate social responsibility - Nguyen Thi Hoa Hong; Truong Thi Hanh; Nguyen Quynh Anh; Dang Ngoc Anh; Tran Minh Ngoc; Nguyen Duong Lan Nhi (Cogent Business & Management, 2024)
This study examines the relationships between Green Human Resources Management and employees' intention to engage in environmentally responsible behaviors. Conducted within the context of 380 employees in Vietnam, a developing country, the research collected data from these workers, which were processed using SmartPLS. The research results indicated that Green Human Resources Management has a positive impact on employees' green behavioral intention and also highlighted the moderating impact of individual green values and the mediating role of Corporate Social Responsibility. These results offer invaluable guidance for organizations seeking to cultivate environmental sustainability through effective HRM practices. Simultaneously, they emphasize the importance of promoting social responsibility and enhancing business performance within the unique Vietnamese business landscape. This research underscores the pivotal role HRM plays in steering organizations towards a greener and more socially responsible future, particularly in emerging economies like Vietnam.
Keywords: M12; M14; M54; Q01; 650; corporate social responsibility; green behaviors; green behavioral intentions; green human Resources Management; green values